IMPROVING THE WRITING SKILL OF THE SECOND GRADERS OF MTS NAHDLATUL WATHAN 2 RENSING LOMBOK THROUGH THE PICTURE WORD INDUCTIVE MODEL STRATEGY - Syamsul Rizal (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2017)
The problem of this research was how to improve the students’ ability to write English using the picture word inductive model strategy. The research type was a collaborative action research. The subject consisted of 26 students of the second graders of MTs NW 2 Rensing Lombok. The research data were collected using four kinds of instruments, which were the writing tasks, observation checklist, field notes, and a set of questionnaires for collecting data on the students’ ability in improving the students’ ability to write English using the picture word inductive model strategy. The reflection was based on the findings during the observation and compared to the criteria of success including: (1) by using the writing tasks, the students’ writing achievement improved (≥75% students of the class achieved the score greater than or equal to 60 of the range that lies from 0-100), and (2) by using an observation checklist and field notes, the students were actively involved in the ten writing activities. The findings indicated that using the picture word inductive model strategy was one of the strategy could improve students’ ability in writing descriptive paragraphs. After the researcher conducted the first and the second cycle, it was shown that the result of the first and second cycle improved